Characteristics of Two Lagoons in the Coastal Area of the Baltic Sea - Oskars Purmalis; Laura Grinberga; Linda Dobkevica; Agnija Skuja; Davis Ozolins; Ivars Druvietis; Viesturs Ozols; Jana Paidere (Limnological Review, 2024)
The proposed study is focused on an ecological analysis of Latvian coastal lagoons, emphasizing their unique but vulnerable nature. Coastal lagoons are recognized as fragile ecosystems of significant ecological, social, and economic value, as recognized by the European Directive 92/43/EEC (Habitats Directive). Despite their protected status, the existence of these ecosystems can be threatened by morphological, hydrological, and anthropogenic changes. The uniqueness of these ecosystems can be determined by the large number of influencing factors and their dynamics. They are affected by seawater, their level of fluctuation, wind exposure, overgrowing with macrophytes, freshwater sources, and water flow generated streams affecting sediment transport and accumulation. All the influencing factors determine a highly trophic ecosystem, which in the studied lagoons is rated as medium to poor ecological status, which confirms the above-mentioned vulnerability and fragility. The aim of this study was to analyze two lagoons in the coastal area of the Baltic Sea in the Riga Gulf, by characterizing, for the first time, their current conditions and ecological parameters because understanding such ecosystems is only partial. The physicochemical composition of lagoon sediments and water shows the impact of seawater by increased electrical conductivity and the concentration of SO42− and Cl− in water, while the presence of detritus in sediments is almost non-existent; thus, the content of organic matter is low with relatively variable pH. The results show that the diversity of studied benthic macroinvertebrates, macrophytes, zooplankton, and even phytoplankton species is low, but there is higher diversity in lagoons and their parts with regular water exchange with the sea. The study provides valuable insight into the ecological dynamics of coastal lagoons in Latvia, shedding light on their current conditions, anthropogenic impact, and the need for sustainable management measures.